Walnut (Juglans regia L.): genetic resources, chemistry, by-products - Martinez, Marcela Lilian (2010)
Walnut (Juglans regia L.) is the most widespread tree nut in the world. There is a great diversity of genotypes differing in forestry, productivity, physical and chemical nut traits. Some of them have been evaluated as promising and may serve as germplasm sources for breeding. The nutritional importance of the nut is related to the seed (kernel). It is a nutrient-dense food mainly owing to its oil content (up to 740 g−1 in some commercial varieties), which can be extracted easily by screw pressing and consumed without refining. Walnut oil composition is dominated largely by unsaturated fatty acids (mainly linoleic together with lesser amounts of oleic and linolenic acids).Minor components of walnut oil include tocopherols, phospholipids, sphingolipids, sterols, hydrocarbons and volatile compounds. Phenolic compounds, present at high levels in the seed coat but poorly extracted with the oil, have been extensively characterised and found to possess strong antioxidant properties. The oil extraction residue is rich in proteins (unusually high in arginine, glutamic and aspartic acids) and has been employed in the formulation of various functional food products. This review describes current scientific knowledge concerning walnut genetic resources and composition as well as by-product obtainment and characteristics.